2019
DOI: 10.3390/ma12152384
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Concrete Permeability by Using Hydrophilic Blended Additive

Abstract: Crystalline hydrophilic additives are increasingly used as efficient methods for reducing water permeability in concrete. Their effectiveness in hindering water penetration has been proven in different cementitious materials, although scarce information has been reported concerning their action mechanism. In the present work, the efficacy of a hydrophilic blended crystalline mix (Krystaline Add1) as a water-reducing additive has been confirmed. Furthermore, an extended study about how the presence of the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…Overall, differences were observed between hydration products forming in the presence of CWA, but their differences were not substantial. XRD results from [52] showed that there has not been any significant difference detected between control and CWA concrete samples and in fact, the relative intensity of the CH and ettringite peaks was very similar in all the cases. This finding is in contrary to obtained EDX results in this study which observed differences between chemical elements and morphology presented in different admixtures.…”
Section: Eds Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Overall, differences were observed between hydration products forming in the presence of CWA, but their differences were not substantial. XRD results from [52] showed that there has not been any significant difference detected between control and CWA concrete samples and in fact, the relative intensity of the CH and ettringite peaks was very similar in all the cases. This finding is in contrary to obtained EDX results in this study which observed differences between chemical elements and morphology presented in different admixtures.…”
Section: Eds Resultsmentioning
confidence: 84%
“…Other cementitious composites with different admixture (P and X) types were also investigated to understand the exact chemical compositions of these crystals (ettringite or not). The formation of ettringite or other calcium sulfo-aluminate hydrate when using CWA was dismissed according to the BSEM and XRD results obtained in the [52] study. The results obtained from the EDS spectra for X and P admixtures indicated that not all admixtures can possibly develop needle-like crystals-acting as a physical membrane-which have different compositions from ettringite.…”
Section: Eds Resultsmentioning
confidence: 99%
“…Crystalline admixtures (CAs) are proposed as an effective alternative for waterproofing concrete when watertight conditions are needed [1]. Their action mechanism is based on the ability for reacting with the water and cement particles, increasing the density of the solid matrix in concrete [2,3] and hindering the penetration of external water into the structure [4]. The full waterproofing effect of concrete prepared with a crystalline admixture has been reported to occur several days after casting [5].…”
Section: Introductionmentioning
confidence: 99%
“…Different aspects on the waterproofing performance of concrete incorporating crystalline admixtures have been evaluated by water absorption tests [6], chloride penetration [7] and permeability tests [2,3]. It has been reported that the efficiency of these compounds in preventing water penetration into the concrete is related to their ability react with portlandite (CH) promoting the formation of non-soluble compounds and sealing the pores inside the concrete bulk [8].…”
Section: Introductionmentioning
confidence: 99%
“…The waterproofing efficiency of CAs has been reported by different authors [5][6][7][8] using permeability tests at the laboratory. The increase of the impermeabilization with time has been observed when hydrophilic blends are used as crystalline admixtures [5]. These tests for the assessment of the waterproofing ability associated to the additive presence are carried out at specific curing ages, and under controlled testing conditions [6].…”
Section: Introductionmentioning
confidence: 99%